Smoking behaviour and knowledge of the health effects of smoking in patients with inflammatory bowel disease. Issue 11 (4th October 2015) - De Bie, C.; Ballet, V.; Hendriks, N.; Coenen, S.; Weyts, E.; Van Assche, G.; Vermeire, S.; Ferrante, M.
Summary: Background: The detrimental effect of smoking on development and progression of Crohn's disease (CD) is generally accepted. Aim: To evaluate the awareness of smoking risks in a Belgian inflammatory bowel disease (IBD) population. Methods: In the out‐patient clinic of a tertiary referral centre, 625 consecutive patients with CD, 238 patients with ulcerative colitis (UC) and 289 non‐IBD controls, filled out a simple questionnaire. This questionnaire included data on smoking behaviour and awareness of smoking‐related health effects, including effects on IBD. Results: At diagnosis, more CD patients were active smokers compared to UC (40% vs. 17%, P  < 0.001). Remarkably, smoking cessation rates after diagnosis were similar for CD and UC (both 56%, P  = 0.997). The great majority recognised a detrimental influence of smoking on general health (98–99%), lung cancer (95–97%), myocardial infarction (89–92%) and stroke (78–87%). Although CD patients more frequently acknowledged risks of smoking on their disease, only 37% were aware of a link with CD development, 30% of increased surgical rates and 27% of increased post‐operative CD recurrence. Active smokers more frequently denied an increased risk of surgery and higher post‐operative CD recurrence. Intriguingly, within the active smokers with CD, those not willing to quit smoking most often denied a potential bad influence of smoking. Taking into account disease duration, previous surgery, education level, working status and nicotine dependence, we were unable to define specific subgroups of patients requiring extra education. Conclusion: Although patients with Crohn's disease were better informed on the detrimental effects of smoking, the awareness rate was still low.